EVALUATION OF POST-OPERATIVE PAIN AFTER VENTRAL HERNIA REPAIR - AWAN , Z; AWAN , H; SAEED , N (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in Nishtar Medical Hospital from January 2022 to January 2023 to assess short-term post-operative pain following laparoscopic and open ventral hernia repair. A total of 50 patients fulfilled the inclusion criteria and were included in the study. Surgical options were explained to all participants, and the open or laparoscopic technique was performed based on the patient’s choice. Post-operative data were recorded, including pain, wound and systemic complications, post-operative hospital stay, and need for ICU care and drain removal day. A visual analog scale (VAS) was used for measuring post-operative pain scores. Patients were followed up for 1 month. Results showed that the post-operative pain score calculated after the open repair was 5.48 ± 2.25, and after laparoscopic ventral hernia repair was 6.05 ± 1.98. Though the laparoscopic technique was associated with higher scores, this difference was statistically insignificant (P= 0.292). Follow up of patients after one month showed laparoscopic repair was associated with lower complications, including pain, infection, seroma, and hematoma, compared to open repair. It can be concluded that laparoscopic hernia repair leads to lesser complications than the open technique. Using sutures and trackers in laparoscopic technique can result in relatively higher post-operative pain in the short term, but this difference is insignificant, due to which laparoscopic ventral hernia repair is more feasible.